Reliability Estimation of Oil and Gas Trunk Pipelines on a Stochastic Heterogeneous Base - Onyshchenko, Volodymyr; Pichugin, Sergiy; Vynnykov, Yuriy; Vynnykov, Pylyp (International Journal of Engineering and Technology, 2018)
The article discusses buried oil and gas pipeline linear part reliability. Reliability parameters are longitudinal and hoop stresses in the pipeline wall, which are caused by the impact of the soil base uneven deformations, operating pressure and temperature difference. Estimation of the pipeline reliability in soils without special properties was performed. Improving the probabilistic solution of the differential equations curved pipe axis was carried out. Numerical FEM modelling was proposed for modelling system “pipeline – collapsible basis”. It gives the most relevant and simplest results. The most dangerous cases of the system deformations were defined by increasing the soaking area of the base. Justification of the distribution laws was performed for the input parameters of the pipeline reliability function. Field studies allowed us to obtain 200 random variables of the mechanical characteristics of the pipeline collapsible bases in a water-saturated state. The pipeline reliability in collapsible strata with different thickness was estimated. There were established dependencies for pipeline strength and reliability laid in soil conditions without special properties, estimated that small deformations do not require an increase in the thickness of a pipeline wall, but the growth of deformations leads to reduction in the pipeline reliability. It is necessary to ensure normative reliability, almost linear increasing in the pipeline wall.